40.2: Efficiency Enhancement in Phosphorescent and Fluorescent OLEDs Utilizing Energy Transfer From Exciplex to Emitter. Issue 1 (June 2015) - Seo, Satoshi; Takahashi, Tatsuyoshi; Nowatari, Hiromi; Hosoumi, Shunsuke; Ishisone, Takahiro; Watabe, Takeyoshi; Mitsumori, Satomi; Ohsawa, Nobuharu; Yamazaki, Shunpei
Abstract : This paper discusses the effectiveness of energy transfer from an exciplex to an emitter in both phosphorescent and fluorescent OLEDs. This energy transfer enhances the efficiency, lowers the drive voltage, and extends the lifetime. The increase in the quantum efficiency of a fluorescent OLED using this mechanism is also analyzed.